PENGARUH PERHATIAN TERBAGI TERHADAP KESADARAN SITUASI - Ariana, Prisca Dwi; Hastjarjo, Thomas Dicky (Jurnal Psikologi, 2018)
The increasing number of traffic accident is caused by the decreasing of driver situational awareness. Divided attention is one of several factors that affect situation awareness. This experiment was to study the effects of listening to the music or reading short message sent to participant’s mobile phone on participant’s situational awareness while they drove car simulator. Thirty subjects were randomly divided into two groups, namely: (a) music group. The subjects were asked to listen to Ed Sheeran pop music when they drove city car simulator, and (b) mobile phone group. In this condition the subjects received and replied short message on their mobile phones at third, fifth, eighth, and tenth minutes during driving car simulator. Situational awareness was measured by SAGAT (Situation Awareness Global Assessment Technique). The simulation was stopped when SAGAT questionnaire was distributed to the subjects at fifth and tenth minutes. The t test statistical analysis showed that there was a significant difference in situation awareness between the two groups (t= 5.750; p= .001). Music group showed higher situation awareness than mobile phone group. The use of mobile phone while driving is more distracting attention than listening to music.